2021
DOI: 10.1093/femsmc/xtab016
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the effectiveness of oxathiapiprolin towardPhytophthora agathidicida, the causal agent of kauri dieback disease

Abstract: Phytophthora species cause disease and devastation of plants in ecological and horticultural settings worldwide. A recently identified species, P. agathidicida, infects and ultimately kills the treasured kauri trees (Agathis australis) that are endemic to New Zealand. Currently there are few options for managing kauri dieback disease. In this study, we sought to assess the toxicity of the oomycide oxathiapiprolin against several life cycle stages of two geographically distinct P. agathidicida isolates. The eff… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 35 publications
1
12
0
Order By: Relevance
“…The EC 50 values reported here are consistent with those of other pathogenic Phytophthora species (Gray et al 2018, Belisle et al 2019. Furthermore, the EC 50 value reported for oxathiapiprolin inhibition of P. agathidicida mycelial growth is in agreement with that from a recent study (Lacey et al 2021).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The EC 50 values reported here are consistent with those of other pathogenic Phytophthora species (Gray et al 2018, Belisle et al 2019. Furthermore, the EC 50 value reported for oxathiapiprolin inhibition of P. agathidicida mycelial growth is in agreement with that from a recent study (Lacey et al 2021).…”
Section: Discussionsupporting
confidence: 92%
“…As has been widely found, Phytophthora pathogens appear to be most sensitive to oxathiapiprolin when compared with ethaboxam, fluopicolide, and mandipropamid (Qu et al 2016, Gray et al 2018, Belisle et al 2019. A recent report of oxathiapiprolin activity against P. agathidicida zoospores and oospores found that this fungicide was also highly toxic to other P. agathidicida life cycle stages (Lacey et al 2021). Thus, it would be pertinent to screen ethaboxam, fluopicolide, and mandipropamid against P. agathidicida spores to characterise differences in fungicide sensitivity across life cycle stages of this pathogen, which could inform potential application methods.…”
Section: Discussionmentioning
confidence: 93%
“…Additionally, their thick cell walls help them withstand harsh environmental conditions and remain resistant to chemical treatments such as sterigene (Bellgard et al, 2010; Dick & Kimberley, 2013). To the best of our knowledge, only disinfectants such as Janola (sodium hypochlorite, active ingredient; Bellgard et al, 2010; Dick & Kimberley, 2013), Virkon S (dipotassium peroxodisulphate; Bellgard et al, 2010; Dick & Kimberley, 2013) and the antibiotic oxathiapiprolin (Lacey et al, 2021) have shown any noticeable activity against oospores of P . agathidicida .…”
Section: Discussionmentioning
confidence: 99%
“…Continuous use also leads to Phytophthora developing resistance to the treatments (Dobrowolski et al, 2008; Hunter, Williams, et al, 2018). Additionally, they are not biodegradable and none of these compounds except oxathiapiprolin (Lacey et al, 2021) are reported to be active against multiple life stages of Phytophthora (Dick & Kimberley, 2013). Resistance to oxathiapiprolin by some Phytophthora has been reported since its approval as a fungicide in 2016 (Miao et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…P. agathidicida oospores were prepared as described previously (Lacey et al 2021). Briefly, cultures were grown in 4% w/v clarified V8 broth supplemented with 30 µ g/ml β-sitosterol (Sigma-Aldrich, St. Louis, Missouri) and incubated in the dark at 22 °C for 4 to 6 weeks.…”
Section: Methodsmentioning
confidence: 99%